Dynamic kinetic resolution-mediated synthesis of C-3 hydroxylated arginine derivatives - Ye Zheng; Zhenyu Chen; Guy J. Clarkson; Stephen A. Marshall; Jianliang Xiao; Christopher J. Schofield; Martin Wills; Andrew V. Stachulski (Royal Society Open Science, 2025)
Hydroxylated amino acids and their derivatives, including those found in proteins, are important in biology and medicinal chemistry. Incubation of N-acetyl-l-arginine with clavaminic acid synthase, a key oxygenase in clavulanic acid biosynthesis, affords a (3R)-hydroxylated product that is identical to material obtained by total synthesis from Boc-beta alanine. The key step employed dynamic kinetic resolution (DKR) of a β-ketoester precursor, achieved in high diastereomeric and enantiomeric excess using an (R)-SEGPHOS/Ru(II) catalyst. The results highlight the utility of DKR for the preparation of C-3 hydroxylated amino acid derivatives.